Molecular detection of tumor cells in regional lymph nodes is associated with disease recurrence and poor survival in node-negative colorectal cancer: a systematic review and meta-analysis - Rahbari, Nuh Nabi; Bork, Ulrich; Büchler, Markus W.; Koch, Moritz; Weitz, Jürgen (Journal of clinical oncology, 2012)
Purpose Up to 25% of patients with node-negative colorectal cancer (CRC) on conventional histopathologic analysis ultimately die of recurrent disease. We performed a systematic review with meta-analyses to clarify whether molecular detection of isolated tumor cells or micrometastases in regional lymph nodes indicates high risk of disease recurrence and poor survival in node-negative CRC. Methods The following databases were searched in August 2011 to identify studies on the prognostic significance of molecular tumor-cell detection in regional lymph nodes of node-negative CRC: MEDLINE, BIOSIS, Science Citation Index, EMBASE, CCMed, and publisher databases. We extracted hazard ratios (HRs) and associated 95% CIs from the identified studies and performed random-effects model meta-analyses on overall survival, disease-specific survival, and disease-free survival. Results A total of 39 studies with a cumulative sample size of 4,087 patients were included. Immunohistochemistry, reverse transcriptase polymerase chain reaction, and both techniques were applied in 30, seven, and two studies, respectively. Thirteen studies were graded with low risk of bias. Meta-analyses revealed that molecular tumor-cell detection in regional lymph nodes was associated with poor overall survival (HR, 2.20; 95% CI, 1.43 to 3.40), disease-specific survival (HR, 3.37; 95% CI, 2.31 to 4.93), and disease-free survival (HR, 2.24; 95% CI, 1.57-3.20). Subgroup analyses showed the prognostic significance of molecular tumor-cell detection of being independent of the applied detection method, molecular target, and number of retrieved lymph nodes. Conclusion Molecular detection of occult disease in regional lymph nodes is associated with an increased risk of disease recurrence and poor survival in patients with node-negative CRC.